2023
DOI: 10.1088/1361-6382/aceacd
|View full text |Cite
|
Sign up to set email alerts
|

Shadows and photon rings of regular black holes and geonic horizonless compact objects

Abstract: The optical appearance of a body compact enough to feature an unstable bound orbit, when surrounded by an accretion disk, is expected to be dominated by a luminous ring of radiation enclosing a central brightness depression typically known as the shadow. Despite observational limitations, the rough details of this picture have been now confirmed by the results of the EHT Collaboration on the imaging of the M87 and Milky Way supermassive central objects. However, the precise characterization of both features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…In this section, we aim to investigate how the plasma background affects the black hole shadow in EBR gravity. The main motivation for this is the idea that in most cases, black holes are surrounded by a medium that changes the geodesic of photons [24,36]. We begin by considering a plasma with a refractive index , where ω denotes photon frequency.…”
Section: Plasma Effects On the Shadow In Ebr Gravitymentioning
confidence: 99%
“…In this section, we aim to investigate how the plasma background affects the black hole shadow in EBR gravity. The main motivation for this is the idea that in most cases, black holes are surrounded by a medium that changes the geodesic of photons [24,36]. We begin by considering a plasma with a refractive index , where ω denotes photon frequency.…”
Section: Plasma Effects On the Shadow In Ebr Gravitymentioning
confidence: 99%
“…On the other hand, theoretical investigations of shadow images of compact objects are quite fascinating. This applies not only to black holes in General Relativity [36][37][38][39][40][41][42][43][44][45] and in alternative gravities [46][47][48][49][50][51][52][53][54][55][56], but also to exotic compact objects like wormholes [57][58][59][60][61][62][63][64][65][66][67], naked singlarities [68][69][70][71][72][73][74][75][76][77][78] or boson stars [79,80]. Previous studies have shown that some of these exotic compact objects can mimic black holes with respect to their shadow images if their light ring properties are similar.…”
Section: Jcap05(2024)007mentioning
confidence: 99%
“…In fact, certain UCOs have the potential to create a shadow resembling that of a BH [53][54][55][56][57][58][59]. Therefore, it is imperative to develop a methodology capable of discerning BHs from other UCOs, such as worm-holes [60][61][62][63][64][65][66][67][68][69][70][71][72][73] and boson stars [74][75][76][77]. As an innovative attempt, Wang et al studied the optical appearance of an asymmetric thin-shell wormhole (ATSW), demonstrating that the shadow of the ATSW exhibits a smaller size compared to that generated by a BH [60].…”
Section: Introduction M87 *mentioning
confidence: 99%